Mekanisme Pasar Dalam Perspektif Islam (Kajian Pemikiran Abu Yusuf) - Moh Agus Sifa' (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Market Mechanisms in the development of the Economy there have been many innovations carried out by modern economic figures. In this case the market mechanism that develops a lot is the difference between the modern mechanism with the mechanism of Islamic economic thought, where Islamic economic thinkers first introduced the market mechanism especially by Islamic economic thinker Abu Yusuf, recorded as the earliest scholars who began to allude to the market mechanism. In terms of market mechanism Abu Yusuf gives a different view to public opinion, where high prices do not mean there is scarcity of goods and cheap prices do not mean abundant goods, but there are other variables that determine price formation. Abu Yusuf also opposed the authorities in setting prices. But he also allows price intervention in the market in certain circumstances. Abu Yusuf said that the price level does not only depend on demand but also on the strength of supply. Therefore, an increase or decrease in the price level does not necessarily have to be related to an increase or decrease in production alone. Keywords: Market mechanism, Abu Yusuf Economic Thought